Coexistence of atopic dermatitis and skin picking disorder in a 5-year-old child. - Özer, M.; Arslan, H.; Bostancı, İ. (European Journal of Pediatric Dermatology, 2021)
Skin picking disorder (SPD) is not a dermatological problem but a clinical picture causing a damage on the skin tissue and characterized by picking the skin intensely and repetitively. Psychiatric disorders such as depression, bipolar disorder and obsessive-compulsive disorder can play a role in its etiology. Neurodermatitis is included in the skin picking disorder spectrum and can be considered its synonym. Clinically, it is characterized by single or multiple lichenified plaques, which are often hyperpigmented and excoriated, and accompanied by prominent skin lines. The psychiatric factors play a role also in nodular prurigo, which is characterized by severely itchy nodules. A 5-year-old male patient, who had been diagnosed with atopic dermatitis, was brought to our outpatient clinic by his family with the complaints of compulsive scratching, which was responsible for severe bleeding. The patient was diagnosed with nodular prurigo/neurodermatitis with SPD. The rarity in the pediatric literature of case reports discussing the association with SPD in a frequently encountered clinical picture such as atopic dermatitis creates a concern that SPD cases are not diagnosed in children. This case has been presented to attract attention to the fact that atopic dermatitis and SPD can be observed together although they are two different clinical pictures and to underline that there should be no delay in diagnosis of SPD since there are also psychiatric disorders in the background.